In reply to the letter to the editor regarding "Clinical outcomes of teeth adjacent to the site of mandibulotomy or mandibulectomy in patients with head and neck cancer: results from a multidisciplinary mono-institutional head and neck tumor board" - Cosimo Rupe; Raffaella Castagnola; Gioele Gioco; Giovanni Almadori; Jacopo Galli; Luca Tagliaferri; Alessandra Cassano; Patrizia Gallenzi; Carlo Lajolo (BMC, 2024)
Abstract This paper aims to reply to Somay et al., regarding their comment to a previous paper from our group, titled "Clinical outcomes of teeth adjacent to the site of mandibulotomy or mandibulectomy in patients with head and neck cancer: results from a multidisciplinary mono-institutional head and neck tumor board". The following concerns were addressed: 1) Within the limits of a case series, mandibulectomy might be considered a risk factor for the loss of tooth vitality as well as mandibulotomy. 2) Root canal therapy before surgery on the teeth adjacent to the surgical site could be an appropriate strategy, although in some cased it may involve teeth which are not destinate to have endodontic complications. 3) Dose-volume data of the included teeth were provided: the impact of radiotherapy (RT) as a confounding factor seems not to be as relevant as Somay et al. have pointed out.